2009
DOI: 10.1007/s11255-009-9568-3
|View full text |Cite
|
Sign up to set email alerts
|

Oral tamoxifen citrate treatment is more effective in normogonadotropic patients who have follicle-stimulating hormone levels within the lower half of normal

Abstract: This study revealed that initial FSH values can be used as a marker to estimate the probability that a patient will benefit from oral TC therapy. Patients in the lower FSH group had statistically higher chances of having higher sperm counts after treatment, and it is rational to advise these patients to receive 6 months of oral TC therapy. However, before drawing firm conclusions from this retrospective study, these results should be confirmed with double-blind, placebo-controlled, randomized trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…In line with prior findings, we revealed increased serum levels of testosterone, FSH and LH after 3 months of treatment in our cohort of patients, which clearly emphasizes the use of tamoxifen in iOAT. Furthermore, 2 prior studies pointed out that the elevated FSH and testosterone serum levels were associated with the use of tamoxifen [4,15]. In our study, we confirmed the predictive role of FSH serum levels prior to treatment with tamoxifen regarding the improvement of sperm parameters: improved sperm motility was shown at lower serum levels of FSH before the start of treatment with the ideal cut-off value of 8.8 mIU/mL.…”
Section: Discussionsupporting
confidence: 86%
“…In line with prior findings, we revealed increased serum levels of testosterone, FSH and LH after 3 months of treatment in our cohort of patients, which clearly emphasizes the use of tamoxifen in iOAT. Furthermore, 2 prior studies pointed out that the elevated FSH and testosterone serum levels were associated with the use of tamoxifen [4,15]. In our study, we confirmed the predictive role of FSH serum levels prior to treatment with tamoxifen regarding the improvement of sperm parameters: improved sperm motility was shown at lower serum levels of FSH before the start of treatment with the ideal cut-off value of 8.8 mIU/mL.…”
Section: Discussionsupporting
confidence: 86%
“…Tamoxifen not only has antagonistic effects on hypothalamic ERs but also has peripheral agonist effects that can decrease bone turnover and increase bone mineral density [109]. Tamoxifen has also been shown to raise T levels and may be effective in the treatment of male infertility [110] but does not seem to affect sexual function in healthy young men [86]. Further research is needed to determine how peripheral estrogenic effects of SERMs relate to male sexual function in the setting of T deficiency.…”
Section: Clinical Implications Of Elevated Estrogensmentioning
confidence: 99%
“…A recent article suggests a better effect of TMX in patients with low FSH levels before starting the therapy [57] suggesting the need for a well-functioning hypothalamic-pituitary-gonadal axis.…”
Section: Treatment For Infertile Men With Idiopathic Oligo-/azoospmentioning
confidence: 99%